The importance of partnerships in building knowledge networks for P-PD scaling: Emerging partnerships for scaling the pioneer positive deviance approach - Habermann, Birgit; Kiptoo, Emmaculate; Maiyo, Nathan; Gichuki, Leah; Worku, Tigist; Getahun, Elizabeth (International Livestock Research Institute, 2024)
Partnerships are a key component of the P-PD approach. Adaptation pioneer households (APHs) and organizations such as government entities, NGOs, dairy cooperatives, private businesses, and other farmers interact and form interconnected partnerships dubbed ‘knowledge network’. A central pillar of such networks is social inclusion, ensuring that diverse farmers have access to knowledge, opportunities, and resources. APHs often serve as catalysts of social inclusion, where household members are used in sharing their innovations and insights with other households.